1984
DOI: 10.1111/j.1476-5381.1984.tb10095.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of noradrenaline and acetylcholine on electro‐mechanical properties of the guinea‐pig portal vein

Abstract: 1 Effects of acetylcholine (ACh) and noradrenaline (NA) on mechanical properties of smooth muscle cells of the guinea-pig portal vein were investigated using intact and skinned muscle preparations. In some preparations, the electrical activity was also recorded. In addition to ACh and NA, the effects of caffeine, procaine, excess concentrations of [K]0 and MnCl2 were investigated. 2 NA enhanced the mechanical response due to increase in the spike generation, receptor activated depolarization and release of Ca … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In portal vein smooth muscle, stimulation of a1-adrenoceptors produces contraction that involves release of Ca2+ from intracellular stores and Ca2 + influx through voltage-dependent Ca2 + channels (Mironneau & Gargouil, 1979;Dacquet et al, 1987). The NAinduced contraction is associated with a depolarization and an increase in membrane conductance (Takata, 1980;Nanjo, 1984). Recent results obtained from single venous smooth muscle cells indicated that the NA-induced depolarization is mainly mediated by an increase in chloride conductance (Byrne & Large, 1988a;Van Helden, 1988;Pacaud et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In portal vein smooth muscle, stimulation of a1-adrenoceptors produces contraction that involves release of Ca2+ from intracellular stores and Ca2 + influx through voltage-dependent Ca2 + channels (Mironneau & Gargouil, 1979;Dacquet et al, 1987). The NAinduced contraction is associated with a depolarization and an increase in membrane conductance (Takata, 1980;Nanjo, 1984). Recent results obtained from single venous smooth muscle cells indicated that the NA-induced depolarization is mainly mediated by an increase in chloride conductance (Byrne & Large, 1988a;Van Helden, 1988;Pacaud et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that caffeine displaces calcium from intracellular stores in portal vein smooth muscle (Nanjo, 1984) and we studied the effects of bath-applied caffeine in caesium-containing solution.…”
Section: Calcium-dependence Of the Noradrenaline-induced Inward Currentmentioning
confidence: 99%
“…In the present study we have investigated the ionic mechanisms underlying the depolarization to noradrenaline (Nanjo, 1984) in cultured single cells isolated from rat portal vein using whole-cell recordings with patch-pipettes.…”
Section: Introductionmentioning
confidence: 99%
“…In Ca2"-free, 0.5 mM EGTA-containing solution, the 60 mM K+-induced contraction ceased within several seconds. In contrast, noradrenaline-and acetylcholine-induced contractions decreased in amplitude but persisted longer (Nanjo, 1984;Dacquet et al, 1987). In the following experiments, the filling of the internal calcium store was carried out on quiescent preparations (in the presence of 50 nM nifedipine) for Omin in 2.1 mM Ca2"-containing solutions.…”
Section: Electrical Activitymentioning
confidence: 99%
“…Spironolactone was a gift from Searle (Paris). Spironolactone and nifedipine were prepared as a 10-' M stock solution in dimethylsulphoxide (DMSO, Sigma) and diluted to the final concentra- Application of a 60mM K' solution induced a phasic peak contraction followed by a sustained plateau the amplitude of which was dependent on the external calcium concentration (Gabella, 1968;Nanjo, 1984). Spironolactone was then added for its equilibration time either before the phasic potassium contraction or during the plateau of the potassium contraction.…”
Section: Electrical Activitymentioning
confidence: 99%